STRATEGI PENGEMBANGAN OBJEK WISATA BONO KECAMATAN TELUK MERANTI KABUPATEN PELALAWAN - Syahputra, Heryanto; Yuliani, Febri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Department of Tourism CultureYouth and Sports(Disbudparpora) Pelalawan is one of the government agencies thatdeal withthe problems Bono Attractionsin Teluk Meranti District, Pelalawan Regency. In Act No 10 of 2009 ontourism, tourismisa wide range oftourist activities and supported by varietyof facilities and services provided bythe business community, government and local government. Department of Tourism Culture Youth and Sportshas the rightto develop Bono attractions in Teluk Meranti District, Pelalawan Regency. But the problem that occursis transportation infrastructure both on land and at seato reach Bono attractions still experiencing difficulties, especiallyon damaged roads. The aimofthis studywas to determine how the strategy a dopted by the Government in developing Bono attractions in Teluk Meranti District, Pelalawan Regency. To analyzethese problems the authoruses the theory of lena and lina namely theory of Strategy. This research is adescriptive research with qualitative approach, wheredata collection techniqueisby observation and interview swith key informants and snowball sampling to determine the continuation informant. The conclusion that can be drawn from this research that the Tourism Development Strategy Bono Attraction Teluk Meranti District Pelalawan Regency there were still many obstacles, especiallyin the case of damaged roads, infrastructures and financial factors(funding). Thus, the Government focus should priority and contribute to developing Bono Attractions inTeluk Meranti District Pelalawan Regency.Key words: Strategy, management, Bono Attractions